2013
DOI: 10.2174/13894501113146660222
|View full text |Cite
|
Sign up to set email alerts
|

Milk Thistle: A Future Potential Anti-Osteoporotic and Fracture Healing Agent

Abstract: Osteoporosis is a progressive disease of the skeleton characterised by bone fragility due to a reduction in bone mass and possibly to alteration in bone architecture that lead to a propensity to fracture with minimum trauma. Most osteoporotic fractures occur at locations rich in trabecular or cancellous bone and usually related to post menopausal women. Recently, silymarin received attention due to its alternative beneficial effect on bone formation. It is a mixture of flavonoids with powerful antioxidant prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In addition to label indications, many studies have reported the beneficial effects of silymarin for the treatment of several diseases (Fig. ), including sepsis (Kang et al ., ; Toklu et al ., ), burns (Toklu et al ., ), osteoporosis (Kim et al, ; Mohd Fozi et al ., ), arthritis (Gupta et al ., ), hypercholesterolemia (Krecman et al, ; Skottova and Krecman, ), cancer (Singh et al, ; Bosch‐Barrera and Menendez, ; Scavo et al, ; Yurtcu et al, ), viral infections (Lani et al, ), diabetes (Malekinejad et al , ; Soto et al , ; Zhang et al , ; Ebrahimpour Koujan et al , ), Alzheimer's disease (Duan et al, ; Kumar et al, ), and Parkinson's disease (Haddadi et al, ; Lee et al, ). Silymarin treatment likewise attenuated the severity of radiotherapy‐induced mucositis in a clinical trial (Elyasi et al , ).…”
Section: Silymarinmentioning
confidence: 99%
“…In addition to label indications, many studies have reported the beneficial effects of silymarin for the treatment of several diseases (Fig. ), including sepsis (Kang et al ., ; Toklu et al ., ), burns (Toklu et al ., ), osteoporosis (Kim et al, ; Mohd Fozi et al ., ), arthritis (Gupta et al ., ), hypercholesterolemia (Krecman et al, ; Skottova and Krecman, ), cancer (Singh et al, ; Bosch‐Barrera and Menendez, ; Scavo et al, ; Yurtcu et al, ), viral infections (Lani et al, ), diabetes (Malekinejad et al , ; Soto et al , ; Zhang et al , ; Ebrahimpour Koujan et al , ), Alzheimer's disease (Duan et al, ; Kumar et al, ), and Parkinson's disease (Haddadi et al, ; Lee et al, ). Silymarin treatment likewise attenuated the severity of radiotherapy‐induced mucositis in a clinical trial (Elyasi et al , ).…”
Section: Silymarinmentioning
confidence: 99%
“…Therefore, SM is most well known for its antioxidant and chemoprotective effects on the liver [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ] and it is often prescribed and self-prescribed as a complementary and alternative hepatoprotective medicine [ 12 ]. SM is being studied as a hepato-, neuro-, nephro- and cardio-protective ingredient due to its strong antioxidant and tissue regenerative properties [ 12 , 13 , 14 , 15 , 16 , 17 ]. There is a range of recent comprehensive reviews covering various routes and mechanisms of action of SM in animal models and human trials [ 13 , 14 , 15 , 16 , 17 ] very often referring to its antioxidant properties.…”
Section: Introductionmentioning
confidence: 99%
“…SM is being studied as a hepato-, neuro-, nephro- and cardio-protective ingredient due to its strong antioxidant and tissue regenerative properties [ 12 , 13 , 14 , 15 , 16 , 17 ]. There is a range of recent comprehensive reviews covering various routes and mechanisms of action of SM in animal models and human trials [ 13 , 14 , 15 , 16 , 17 ] very often referring to its antioxidant properties. However, it seems likely that direct antioxidant (AO) activity of polyphenols does not contribute directly to the antioxidant defence of the body [ 18 , 19 ] and only limited work has been carried out to explore SM/silybin impact on the induction of cellular antioxidant defence via the modulation of various transcription factors, including Nrf2 and NF-κB and respective gene and protein expressions.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have revealed that it has a strong anti-inflammatory and anti-oxidant effects (Singh & Agarwal, 2009). It is also used as a gold standard drug to treat liver disorders through strong antioxidant properties and tissue regeneration (Mohd Fozi, Mazlan, Shuid, & Isa Naina, 2013).…”
Section: Discussionmentioning
confidence: 99%